2010
DOI: 10.1017/s1355617710000597
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical Effects of Adaptation to Left- and Right-Shifting Prisms Depends on Pre-existing Attentional Biases

Abstract: Proposals that adaptation with left-shifting prisms induces neglect-like symptoms in normal individuals rely on a dissociation between the post-adaptation performance of individuals trained with left- versus right-shifting prisms (e.g., Colent, et al. 2000). A potential problem with this evidence is that normal young adults have an a priori leftward bias (e.g., Jewell & McCourt, 2000). In Experiment 1, we compared the line bisection performance of young adults to that of aged adults, who as a group may lack a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
62
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 38 publications
4
62
4
Order By: Relevance
“…The present results for visual bisection are at odds with some published data which has suggested that older adults show reduced pseudoneglect (Fujii et al, 1995;Stam & Bakker, 1990;Benwell et al, 2014b;Schmitz & Peigneux, 2011;Barrett & Craver-Lemley, 2008;Goedert et al, 2010), so it is necessary to consider why this may be. One speculative candidate may be method: Benwell et al (2014b) and Schmitz & Peigneux (2011) both used variants of the 'Landmark' task, in which judgements are made about a pre-bisected presented line: it may be that this task requires more fine grained perceptual evaluation, and thus elicits higher levels of real or perceived difficulty, , and that this causes additional recruitment of areas in the contralateral hemisphere, which is a clear possibility under the CRUNCH model of aging (Reuter-Lorenz and Cappell, 2008) and may also be so under the HAROLD model (Cabeza, 2002;Cabeza, et al, 1997;2002).…”
contrasting
confidence: 99%
See 3 more Smart Citations
“…The present results for visual bisection are at odds with some published data which has suggested that older adults show reduced pseudoneglect (Fujii et al, 1995;Stam & Bakker, 1990;Benwell et al, 2014b;Schmitz & Peigneux, 2011;Barrett & Craver-Lemley, 2008;Goedert et al, 2010), so it is necessary to consider why this may be. One speculative candidate may be method: Benwell et al (2014b) and Schmitz & Peigneux (2011) both used variants of the 'Landmark' task, in which judgements are made about a pre-bisected presented line: it may be that this task requires more fine grained perceptual evaluation, and thus elicits higher levels of real or perceived difficulty, , and that this causes additional recruitment of areas in the contralateral hemisphere, which is a clear possibility under the CRUNCH model of aging (Reuter-Lorenz and Cappell, 2008) and may also be so under the HAROLD model (Cabeza, 2002;Cabeza, et al, 1997;2002).…”
contrasting
confidence: 99%
“…It should be noted that the minimum age of older adult participants in our study is a little younger than in other comparable visual pseudoneglect studies (e.g. Benwell et al, 2014;Goedert et al, 2010;Learmonth et al, 2015;Nagamatsu,et al, 2011;Schmitz & Peigneux, 2011). These younger participants show a greater left-bias.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…It is possible that a reduction in general alertness/vigilance over the lifespan (Robinson and Kertzman, 1990; Buysse et al, 2005; Nebes et al, 2009; Goedert et al, 2010) may also contribute to the chronic attenuation of pseudoneglect in the elderly.…”
Section: Introductionmentioning
confidence: 99%